Simulation of overland flow and associated sediment loads under low slope sodic soil conditions - PANDEY, RAVI KANT; DENIS, D.M.; VERMA, CHHEDI LAL; ARORA, SANJAY (Journal of Soil and Water Conservation, 2026)
The analysis of rainfall, runoff and sediment load is important to understand the pattern of runoff hydrograph and soil erosion on highly dispersed soil. An experimental setup was developed to simulate surface runoff and soil erosion over a field length of 6 meter and width of 0.44 meter. A rainfall intensity of 60 mm/hr was maintained for period of 36 minutes when runoff rate becomes constant. Runoff was measured for a period of 70 minutes at a regular interval of 4 minute. 88.36 liter (100%) of rainfall occurred, 85 liter (96%) was collected as runoff and 3.36 liter (4%) was infiltration and deep percolation loss. The Rational Function Model explain the runoff hydrograph with R=0.98330373 and S=211.55227726 with peak runoff rate was 2.6 liter after 26 minutes of rainfall initiation. Measured runoff volume was 85.0 liter while modeled runoff volume by Rational Function Model was 86.890 liter showing a great match between observed and modeled runoff values. A Sinusoidal sediment load model explained the variation of sediment load in runoff water against time with R=0.97200951 and S=0.46900781. The sediment load in surface runoff was calculated as 150.240 g (569.09 kg/ha) and modeled 149.281 g (565.46 kg/ha). The modeled sediment load was 99% of calculated silt from runoff that shows a great match.